Prevalence, awareness, treatment, and control of hypertension and associated risk factors among adults in Xi'an, China: A cross-sectional study. Issue 34 (August 2016) - Hu, Meiqin; Wan, Yi; Yu, Lifen; Yuan, Jing; Ma, Yonghong; Hou, Bin; Jiang, Xun; Shang, Lei
Abstract : Abstract: To investigate the prevalence, awareness, treatment, and control of hypertension, and the associated risk factors among adults in Xi'an, China. From October to December 2013, participants in Xi'an, China were recruited for the study by using a multiple-stage sampling method. A self-developed questionnaire with an additional health examination was used to collect data on the history of hypertension diagnosis and antihypertensive medication. The status on prevalence, awareness, treatment, and control of hypertension were analyzed and related risk factors were identified by using logistic regression analysis. A total of 8193 participants were included with an overall prevalence of hypertension of 20.4%. Among the hypertensive participants, 63.7% were aware of their conditions, 47.3% took antihypertensive medication, and 17.8% had their blood pressure (BP) controlled within 140/90 mm Hg. More complications and less frequent BP measurements were associated with hypertension. Older participants, non-drinkers, and those with more complications and more frequent BP measurements were more aware of their hypertension. Being older, living in an urban area, and having more frequent BP measurements were all factors for better treatment. Participants who were women, living in an urban area, with a higher educational level and who were not obese were more likely to have their hypertension controlled. The prevalence of hypertension among adults in Xi'an is high with suboptimal low awareness, treatment, and control rates. Further comprehensive integrated strategies based on these risk factors should be taken into account in order to improve the prevention, awareness, treatment, and control of hypertension.